Pengaruh peran perangkat desa, transparansi, dan sistem pengendalian internal terhadap akuntabilitas pengelolaan dana desa - Maharani Suwu, Pricelia; Murapi, Ikang; Ihyani, Layali (Jurnal Ilmiah Bisnis dan Perpajakan (Bijak), 2025)
The government has currently distributed village funds to every village in Indonesia. Good management of village funds can certainly help a village develop. This study aims to examine and analyze the influence of the role of village officials, transparency, and internal control systems on the accountability of village fund management. A quantitative approach was used through the distribution of questionnaires to village secretaries, village councils, and village communities in Lingsar Subdistrict, West Lombok Regency, with a total of 39 respondents. The results of the study indicate that the internal control system variable influences the accountability of village fund management. However, the variables of the role of village officials and transparency do not influence the accountability of village fund management in Lingsar Sub-district, West Lombok Regency. This finding indicates that the effectiveness of accountability is more determined by the strength of the internal control system than by the role of village officials or transparency.